Turnarounds in high technology firms from a resource based view: A case study - Hulkund, Santosh Mallikarjun (2011)
Corporate turnarounds is widely debated among practitioners, conversely the strategy literature is divided on number of key factors affecting turnaround. Moreover, prior research has essentially concentrated in manufacturing, banking, family business, and few in service industry. However, the high technology sector is largely ignored. Hence, this study explores the role of strategy in turnarounds of high technology firms that have successfully reversed their decline. In addition, this study uses a robust systematic method to identify those firms that can be categorised in high technology domain. Furthermore, the identified firms are examined in a detailed case study approach.